A novel cryoballoon ablation system for eradication of dysplastic Barrett’s esophagus: a first-in-human feasibility study - van Munster, Sanne Noortje; Overwater, Anouk; Raicu, Mihaela G. M.; Seldenrijk, Kees C. A.; Nagengast, Wouter B.; Schoon, Erik J.; Bergman, Jacques J. G. H. M.; Weusten, Bas L. A. M. (Endoscopy, 2020)
Background Endoscopic cryoablation for Barrett’s esophagus (BE) might offer advantages over heat-based ablation. Focal cryoballoon ablation has been promising for short-segment BE, whereas the novel 90°-swipe cryoballoon ablation system (CbSAS90) ablates larger areas in a single step (90° over 3 cm). The system allows for dose adjustment. CbSAS90 has been feasible and safe in animal and pre-esophagectomy studies. This is the first clinical study to assess feasibility, safety, and efficacy of CbSAS90 for eradication of dysplastic BE.Methods In this prospective study in dysplastic BE patients, dose finding started with semi-circumferential treatment at 0.8 mm/s (dose 1). The dose was escalated by reducing speed by 0.1 mm/s in six patients until BE surface regression was ≥ 80 % without complications (“effective dose”). The effective dose was subsequently confirmed with circumferential treatment in 12 new patients. Post-procedural pain (0 – 10) and dysphagia (0 – 4) were evaluated. Outcomes were feasibility, safety, and BE surface regression.Results 25 patients were included, with technically successful treatment in 92 % (95 %CI 73 % – 99 %). Median (95 %CI) BE surface regression was 78 % (50 % – 85 %) for dose 1 and 85 % (55 % – 95 %) for dose 2 (0.7 mm/s), which was defined as the effective dose. Circumferential treatment resulted in 93 % (88 % – 96 %) regression. Two of 12 patients with circumferential treatment developed strictures that required dilation. Median pain and dysphagia scores were low (0 – 3 and 0, respectively).Conclusions CbSAS90 was feasible and effective for ablating larger BE areas. The optimal dose for circumferential treatment that balances safety and efficacy requires further evaluation.